Implementasi Standar Pelayanan Kefarmasian di Apotek - M. Sidrotullah; Nur Radiah (University Of Darussalam Gontor, 2019)
Pharmaceutical work is always developing following the demands of the community so that the patients served understand about the pharmaceutical preparations they receive, and the monitoring system in patients can be carried out well. According to the Minister of Health of the Republic of Indonesia No.73 of 2016, regarding Pharmaceutical Service Standards at the Pharmacy which refers to Pharmaceutical Care, pharmacists are responsible for the quality of medicines given to patients, as well as information on how to use side effects to monitor drug use, to improve quality of life patient. This study aims to determine the description of the implementation of pharmaceutical service standards in pharmacies in the city of Mataram, as well as supporting and inhibiting factors on their implementation. This research is a descriptive study using 52 private pharmacies in 6 sub-districts in the city of Mataram. Data collection was carried out using a questionnaire, referring to Monitoring of Pharmaceutical Services at the Pharmacy, Ministry of Health of the Republic of Indonesia. Assessment includes six standards divided into thirty one parameters. While data on supporting and inhibiting factors are obtained from the results of interviews to respondents. Previously tested the validity and reliability of the questionnaire on 30 respondents using SPSS. The results showed that pharmaceutical service standards at pharmacies in Mataram had not been implemented well, with good categories (≥85) of 0%, medium (65-85) 27%, and less (≤65) 73%. Based on the results of the interview, it is known that the supporting factors for implementing standards are the pharmacist's motivation at work, PSA support and all staff at the pharmacy, support and commitment with relevant stakeholders namely policy makers and regulations, agencies that carry out socialization, monitoring and coaching, universities, professional organizations . While the inhibiting factor is the pharmacist has not played a role in the pharmacy, weak support and evaluation by the pharmacy management, including the procurement of facilities and infrastructure, lack of socialization, legislation, and weak regulatory control by the relevant authorities.